Pluralismo jurídico, multiculturalismoe interculturalidad - Cruz Rodríguez, Edwin (2023)
This paper examines the differences between multiculturalism and interculturalism at a prescriptive level and draws consequences to think about legal pluralism. Both approaches accept the need for formal legal pluralism to achieve egalitarian relations bet ween cultural groups inside a state. However, these approaches have different consequences from a prescriptive perspective. The normative foundations of multiculturalism — tolerance and coexistence among cultural groups and the safeguarding of liberal values — result in an unequal legal pluralism that establishes personal, territorial, and material constraints for the legal systems of non - liberal cultural groups. In contrast, interculturalism, given its emphasis on respect, coexistence, dialogue, and mutual lea rning between cultural groups, as well as its acceptance of the legitimacy of different conceptions of the “good life,” allows an egalitarian legal pluralism to arise, with institutional mechanisms for cooperation between legal systems